E-GOVERNMENT PERFORMANCE IN JORDAN - Al-Onizat, Hamdan Hasan; Oqeili, Saleh; Hijazi, Bassam (European Scientific Journal, ESJ, 2013)
The aim of the study is to explore the process of the evaluation process in the Jordanian e-Government program, The research adopted the quantitative approach to answer the questions of the study, an interviews with the CIOs were conducted to answer the questions of the study. The study found that the lack of the systematic evaluation process is the main factor that the retreating of the e-Government program in Jordan.